Emotional and Behavioral Risk Configurations, Students With Disabilities, and Perceptions of the Middle School Ecology. (September 2020) - Chen, Chin-Chih; Farmer, Thomas W.; Hamm, Jill V.; Brooks, Debbie S.; Lee, David; Norwalk, Kate; Lambert, Kerrylin; Dawes, Molly; Sterrett, Brittany; Rizzo, Karen
Perceptions of the ecology and middle school transition are examined in relation to interpersonal competence patterns (ICPs) of approximately 3, 000 sixth graders (46.2% boys) including 415 students with disabilities from 26 metropolitan schools. Teacher ratings of students' academic competence, externalizing and internalizing behavior, popularity, physical attractiveness/athletic ability, and friendliness are used to determine students' ICPs. Using latent profile analyses, distinct ICPs are identified, including Model (high adaptive), Average, Tough (popular-aggressive), Passive (shy, withdrawn), and Troubled (low adaptive) for boys and girls, respectively. Although students with disabilities are overrepresented in Passive and Troubled ICPs and underrepresented in the Model ICP, 804 students without disabilities (367 boys) were identified in risk ICPs (i.e., Passive, Tough, Troubled) compared with 197 students with disabilities (128 boys). Risk ICPs are differentially associated with students' perceptions of the school ecology and the transition experience of students with disabilities. Implications for Multitiered Systems of Support and the tailoring of interventions are considered.